The mitochondrial genome of Apis mellifera simensis (Hymenoptera: Apidae), an Ethiopian honey bee - Boardman, Leigh (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of Apis mellifera simensis was 16,523 bp long. The 13 protein-coding genes, two rRNAs, and 22 tRNAs resembled other Apis mitogenomes. The location of this Apis subspecies in our phylogenetic tree supported the hypothesis that this subspecies is distinct, and is most closely related to A. m. scutellata and A. m. monticola.